Toward SOA with ESB a real world view from design to implementation. - Borges, Bernhard (SOA webservices journal.)
Enterprises have become increasingly sensitive to the need to become sense and response enabled. That is, enterprises perceive a strategic need to be able to both respond faster and more effectively to, and initiate changes in their environment.